INTERKONEKSI INFORMASI UNTUK STRATEGI KOMUNIKASI PRODUK IPTEK DALAM NEGERI - Dicky Rezady Munaf (Fakultas Seni Rupa dan Desain ITB, 2008)
The strategic position of a nation may determine its existence in the world. The position depends on the ability of the nation to interact internationally. The interaction refers to the communication strategy as a transnational non-territorial actor that is dynamic, universal, and non-political substantive. In implementing the communication strategy, higher educations and the institutions of science and technology needs to optimize their competence as intelligence-based institutions to conduct interconnection presenting the synergy of intelligence to communicate science and technology for human beings. Keyword: transnational non-territorial actor, communication strategy, interconnection, science and technology